PEMETAAN DIALEK BAHASA MAKASSAR DI KABUPATEN BANTAENG (KAJIAN SINKRONIS) - Mardatillah, Rahmi; Apyunita, Devi; Yustina, Ade (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2024)
The study aims at (1) describing the differences in language levels in Makassar dialect lexicon in Bantaeng district and (2) mapping the differences in language levels in Makassar dialect lexicon in Bantaeng district. The type of this study is descriptive qualitative research. The data source of the study was speech community in Bantaeng district. The research data were observation points, each spread in 8 sub-districts in Bantaeng district and 200 basic Swadesh vocabularies with various groupings. The data collection techniques used were face to face conversation, record, and note-taking. The result of the study reveal that there are differences in language levels in lexicon, which discovered 37 concepts and described in map 001 up to map 037 where the speech community in Bantaeng district still loyal to use Makassar language, namely Bantaeng dialect which generally appeared in observation point 2, 6, 7, and 8; whereas, the speech society in observation points 1, 3, 4, and 5 besides using Bantaeng dialect in their daily lives, they also use Lakiung, Turatea, Konjo, and Bira-Selayar dialects. It is because the observation points in the study are directly adjacent to other districts.